Mitigation of salinity stress on morpho-physiological and yield related parameters of rice using different organic amendments - Israt Jahan Irin; Akter, Keya; Rasul, Shishir; Biswas , Tatia; Alam, Md. Mahbubul (Plant Science Today, 2024)
Salinity is a pernicious abiotic element that hinders crop development. Utilizing organic amendments to remediate salt is crucial for enhancing soil function and promoting crop growth. Based on this, a pot experiment was carried out at the research field of Khulna Agricultural University, Khulna, to examine the physiology, growth, and yield of transplanted aman rice in response to salinity stress using duckweed, and dhaincha biomass supplement. Excess salinity with no organic amendments reduced plant growth and development, relative water content (26%), and membrane stability (28%), index compared to T1 S1 (duckweed), and T2 S1 (dhaincha) at 50 mM salinity. Salinity delayed the emergence of first flowering and the maturity of filled grains. The lowest grain yield was recorded in T0S3 (no treatment + 100 mM salinity). Application of dhaincha and duckweed biomass ameliorates salinity individually at all salinity levels. Rice grown in saline soil with the application of T1 (duckweed biomass) and T2 (Sesbania biomass) had an 87% spikelet fertility while rice grown in soil without T1 and T2 treatment had only 21.82%. The application of T2 and T1 @ 5 t ha-1 increased grain yield by 33.29% and 4.70% compared to control. Furthermore, salinity stress @100 mM NaCl with duckweed decreased grain yield by 0.05% which was minimized to 12% by applying dhaincha green manure (T2) @ 5 t ha1. The finding showed that the ameliorative impact of green manure at 5 tha1 dose (T2) was more effective compared to the duckweed (T1) at the three salinity levels used in the study.